Organizational Citizenship Behavior (ocb) Viewed From Servant Leadership and Personality Of Employees at PT. Perkebunan Nusantara VI Business Unit Rimbo Dua, Tebo District - Amran Amran (Baselang, 2022)
Organizations or companies always have various kinds of goals to be achieved. To achieve organizational goals, cooperation between all units or sections within the organization is required. Without cooperation it is difficult for organizations to achieve success. The purpose of this study was to determine the effect of servant leadership and personality on Organizational Citizenship Behavior of PT. Perkebunan Nusantara VI Rimbo Dua Business Unit, Tebo Regency partially and simultaneously. The total population is 47 people and the sample is 47 people using the sampling method using Saturated Sampling. the decision is that H0 is rejected Ha is accepted, it can be concluded that Servant Leadership has a significant effect on Organizational Citizenship Behavior and the personality variable with Organizational Citizenship Behavior shows that tcount = 10.584 is greater than ttable = 2.015 at a significance level of 0.05, so the decision is H0 is rejected Ha accepted, it can be concluded that personality has a significant effect on Organizational Citizenship Behavior. Based on the simultaneous simultaneous test, the Fcount value is 108.461 and the Ftable is 3.21, this indicates that the Servant Leadership and personality variables have a significant effect on the Organizational Citizenship Behavior variable. based on the results of r2 = 0.831 this means that the contribution of Servant Leadership (X1), Personality (X2) to Organizational Citizenship Behavior (Y) is 83.1% and the remaining 16.9% can be explained by other factors outside of this study .